Air sac trematodes: Morishitium polonicum as a newly identified cause of death in the common blackbird (Turdus merula) - Galosi, Livio; Heneberg, Petr; Rossi, Giacomo; Sitko, Jilji; Magi, Gian Enrico; Perrucci, Stefania (International journal for parasitology. Parasites and wildlife, 2019)
Necropsy of two free-ranging common blackbirds (Turdus merula) found dead in central Italy revealed the presence of a high number of cyclocoelid flukes in the coelomatic cavity. Cyclocoelid flukes primarily infect avian respiratory system. Histologically, air sac walls were covered with a fibrinous exudate containing degenerate heterophils, many trematodes and some colonies of Gram-positive cocci. The superficial bronchi and parabronchi were markedly distended, and the adjacent pulmonary parenchyma was congested and collapsed. Trematodes, surrounded by a mild suppurative to pyogranulomatous inflammatory reaction, were also observed on the pericardial, intestinal, kidney and hepatic serosal surfaces. The death of the two examined birds was likely due to the high parasite load and associated severe lesions. At parasitological examination, flukes showed a tongue-shaped elongate body, tapered anteriorly and rounded posteriorly, of 2,088-2,314 μm in width and 8,268-11,830 μm in length. The mouth was slightly oval and sub-terminal, with a small oral sucker. The oval pharynx measured 250-309 μm, and the two caeca joined posteriorly. Two large (550-702 μm × 450-520 μm) globular testes were situated obliquely to each other, whereas an oval (250 × 300 μm in mean) or round (about 334 μm in diameter) intertesticular ovary was placed in a longitudinal straight line with the testes. The ootype was about 110 μm in diameter, while the brown-yellow eggs measured 131.5 × 73.9 μm in mean. The genital pore was post-pharyngeal, while the symmetrically arranged vitelline glands were not confluent posteriorly. Morphoflogical diagnosis led to the identification of Morishitium polonicum, a cyclocoelid fluke species that typically inhabits the air sacs of blackbirds. The morphological diagnosis was corroborated by molecular phylogenetic analysis of the mitochondrial (CO1, ND1) DNA loci. The present study provides the first report of pathological lesions and death caused by M. polonicum in birds.